2023
DOI: 10.7150/ijbs.77133
|View full text |Cite
|
Sign up to set email alerts
|

M6A-modified circRBM33 promotes prostate cancer progression via PDHA1-mediated mitochondrial respiration regulation and presents a potential target for ARSI therapy

Abstract: N6-Methyladenosine (m6A) is the most prevalent RNA modification in various types of RNA, including circular RNAs (circRNAs). Mounting evidence has shown that circRNAs may play critical roles in diverse malignancies. However, the biological relevance of m6A modification of circRNAs in prostate cancer (PCa) remains unclear and needs to be elucidated. Our data showed that circRBM33 was m6A-modified and was more highly expressed in PCa cells than in normal cells/tissues. The in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Among the 11 GRGs examined, GPI is a predictor of outcomes in UCEC patients [36][37][38] as well as other cancers [39][40][41][42] . Similarly, other genes such as HK1 43,44 , PDHA1 [45][46][47] , PGK2 48 , NUP155 49 , PC [50][51][52] , ALDOB [53][54][55][56] , and PFKM 57,58 have been implicated in carcinogenesis and have demonstrated effects on patient prognoses in various cancer types. We observed that PDHA1 and GPI exhibit the highest positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 11 GRGs examined, GPI is a predictor of outcomes in UCEC patients [36][37][38] as well as other cancers [39][40][41][42] . Similarly, other genes such as HK1 43,44 , PDHA1 [45][46][47] , PGK2 48 , NUP155 49 , PC [50][51][52] , ALDOB [53][54][55][56] , and PFKM 57,58 have been implicated in carcinogenesis and have demonstrated effects on patient prognoses in various cancer types. We observed that PDHA1 and GPI exhibit the highest positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The methyltransferase complex is composed of WTAP/METTL3/METTL14, which increases circDDIT4 levels, while FTO exerts the opposite effect ( 125 ). The circRBM33-FMR1 complex stabilizes PDHA1 mRNA in an m 6 A-dependent manner and activates the mitochondrial metabolism of PCa, thereby promoting PCa progression ( 126 ).…”
Section: A and Circrnas In Cancer Metabolismmentioning
confidence: 99%
“…PDHA1 is negatively regulated by activating protein 2 alpha (AP2α) in cervical cancer cells to control aggressive characteristics and aerobic glycolysis 98 . CircRBM33 modified by N 6 ‐methyladenosine (m 6 A) contributes to prostate carcinoma progression through PDHA1‐mediated mitochondrial respiration modulation as well as attenuates the response to androgen receptor signaling inhibitor treatment 99 …”
Section: Cuproptosis a Unique Copper‐induced Cell Death Modality As A...mentioning
confidence: 99%
“…98 CircRBM33 modified by N 6 -methyladenosine (m 6 A) contributes to prostate carcinoma progression through PDHA1-mediated mitochondrial respiration modulation as well as attenuates the response to androgen receptor signaling inhibitor treatment. 99 SIRT3 is a major mitochondrial acetyl-lysine deacetylase and a tumor suppressor in the mitochondria, which deacetylates PDHA1 lysine 321 as well as increases its activity in cancer cells. 100 PGC1α, a central mediator of mitochondrial metabolism, upregulates PDHA1 and MPC1 for reversing the Warburg effects to elevate pyruvate flux into the mitochondria for oxidation, and to promote mitochondrial biogenesis and fusion to control the metabolic transformation to oxidative phosphorylation, thus promoting cholangiocarcinoma metastases.…”
Section: Pdha1mentioning
confidence: 99%